Analysis of ward games using game theory and reaction networks - Paz, Skezeer John B. (Animo Repository, 2022)
We present three models of a symmetric bimatrix game called a "ward game," which exhibits the warding strategies of players in popular multiplayer online battle arena (MOBA) games such as Defense of the Ancients 2 (DOTA 2) and League of Legends (LOL). We analyze the games from the perspective of two opposing players who are maximizing their gold resources by considering each team as one player in every model. Given some conditions on the parameters of a ward game, we establish the set of symmetric Nash equilibria by using the notions of classical game theory. We apply these results in a population setting by identifying the set of evolutionarily stable strategies (ESS) on a repeated ward game by using evolutionary game theory (EGT) concepts. We also use reaction networks to analyze the dynamics of the game, compare some of these results to that of classical game theory and EGT approaches, and identify the best decisions for a player given some conditions on the parameters of the reaction system.